Exploring Tourist Desires: A Journey into Sustainability in Bukit Lawang’s Ecotourism - Nova Bernedeta Sitorus; Liyushiana Liyushiana; Dewi Yanti; Ngatemin Ngatemin (Politeknik Pariwisata Makassar, 2024)
This research aims to understand tourist preferences and evaluate the conditions of sustainable tourism in Bukit Lawang, an ecotourism area known for its rich biodiversity. By utilizing conjoint analysis, the study identifies key attributes important to tourists, aiding managers in designing programs that enhance visitor satisfaction. The research method combines a simple quantitative and qualitative approach, including interviews with tourism business managers, Pokdarwis actors, and local communities, as well as field observations to grasp the dynamics of tourism. A total of 100 respondents were involved through a questionnaire developed on the Gform platform, focusing on preferences related to nature activities, accommodation, and transportation. The analysis results show that teenagers and university students have a high interest in activities such as jungle trekking, creating opportunities for ecotourism development. The majority of respondents come from outside the region, indicating the potential for local tourism growth. Community involvement in tourism management is crucial to preserving the authenticity of culture and the environment. By focusing on tourist preferences and strengthening local participation, Bukit Lawang has the potential to achieve sustainable tourism that benefits all stakeholders. This study provides a guide for stakeholders in formulating responsible tourism policies and creating a successful model for sustainable destination development.